Nanocomposite solar cells based on organic/inorganic (clonidine/Si) heterojunction with plasmonic Au nanoparticles - Mamykin, S.; Mamontova, I.; Kotova, N.; Kondratenko, O.; Barlas, T.; Romanyuk, V.; Smertenko, P. S.; Roshchina, N. (Physics and Chemistry of Solid State, 2020)
The peculiarities of optical and electrical properties of organic(clonidine)/inorganic(Si) heterojunction with plasmonic Au nanoparticles have been investigated by reflection spectra, photoelectric and current-voltage characteristics measurements. Porous nanostructured surfaces of silicon wafers were obtained by the method of selective chemical etching initiated by metal (gold) nanoparticles. Nanocomposites based on nanostructured silicon, clonidine and gold nanoparticles have been made. Two types of structure, namely, solar cells and photodiodes on the basis of such heterojunction were analysed. The reflection spectra of light confirmed the excitation of the plasmon mode in nanocomposites with gold nanoparticles. Photoelectric studies have shown an increase of the photocurrent of solar cells obtained as a result of using both nanostructured silicon and gold nanoparticles in 1.5 and 7 times, respectively. Study of the injection properties of the structures showed that the clonidine layer always facilitates the injection of current carriers, while gold nanoparticles limit the current in the case of a flat surface.